The Royal Navy's Reserves in War and Peace, 1903-2003 - Howarth, Stephen (Barnsley, London Leo Cooper, 2003)
This is the official history marking the centenary of the Royal Navy Volunteer reserve, from their formation in 1903 through their unification with the mercantile Royal Navy Reserve in 1958, and on to their present complete integration with the Royal Navy as the 'part- time element of a single naval service'.
Include Index, Appendix and Illustration
Keywords: Great Britain. Royal Naval Volunteer Reserve -- Great Britain. Royal Navy -- Great Britain. Royal Naval Reserve